Optimization of Foaming and Filling Agents in Foam-Mat Drying Method for Kombucha Powder Production - Farah Fadhilah Widiaputri; Sutrisno S Mardjan; Siti Mariana Widayanti (Jurnal Keteknikan Pertanian, 2026)
Kombucha is a functional beverage produced by fermenting tea with a symbiotic culture of bacteria and yeast (SCOBY).  It is known for its various health benefits but is limited by its short shelf-life. To improve its stability, kombucha can be converted into powder using the foam-mat drying method, the effectiveness of which depends strongly on the formulation of foaming and filling agents. This study aimed to determine the optimal formulation of foaming and filling agents in kombucha. This study evaluated four formulations combining maltodextrin (15% and 20%), Tween-80 (0.25–1%), egg albumen (0–5%), and carboxymethyl cellulose (CMC; 0.3%). The formulation of 500 g kombucha with 15% maltodextrin, 0.3% CMC, 0.5% Tween-80,  and 5% egg albumen produced the best results, yielding 14.38% powder with 5.78% moisture, a hue value of 1.32, chroma of 14.80,  and whiteness index of 81.84. These findings indicate that the selected formulation is effective in producing kombucha powder with desirable physical properties.